A comparative study between the levels of emotional arousal and its relationshipto effective performance of the skill players Basketball - Abbas, Azima (Journal of Physical Education, 2010)
The purpose of research is to identify the levels of arousal of the basketball players, as well as identifying the effectiveness of performance skill to them in addition to the relationship between levels of arousal and effectiveness of performance skill, and may be the research community of basketball players in the Kurdistan region clubs and it’s numbers (5) clubs the researcher chose samples of them by lottery to consist of (3) clubs (Senherib, Sirwan and Gara) at a rate (60%) of the community of origin. As noted by the researcher during the following up of the women’s basketball game that the degree of the level of arousal experienced by the player before the game is one of the things that must be taken into consideration of researchers linked to direct the player’s ability to perform the skill during the game, beside a weak interest in the case of by the trainers because of the paucity of scientific and academic levels of them, the researcher adopted to study this problem on a scale of emotional arousal, which put by (Dorothy Harris and Bet Harris), which he (Osama kamil Rateb) in (1991) prepared image and codification of Arabic, also adopted a researcher the equation developed by the Russian Federation (Berainschi) to measure the effectiveness of performance skill of basketball players with some modifications that were done to fit the rain on the rules of the game from being modified. The researcher used a number of statistical methods for processing the results obtained, such as the arithmetic mean and standard deviation and analysis of variance and simple correlation coefficient - Pearson. After the presentation and discussion of results the researcher reached to a number of conclusions, including that there is an urgent need for attention and psychological care of the players because of the high degree of emotional arousal, and they also show that the level of effectiveness of performance skill has not yet reached the level required to decrease the degree of effectiveness of performance as it turned out that there is a relationship significant inverse correlation between emotional arousal and effective performance of each skill teams research sample and the researcher therefore recommends the adoption of psychological training should be a vital part of the training curriculum for trainers of women’s basketball, especially with regard to arousal emotional and taking into consideration individual differences among players because arousal vary from player to another researcher also recommends need to work on developing basic skills and defensive capabilities as well as concern for the law of basketball knowledge to ensure a high degree of effectiveness of performance skill to have